Projeto integrado de prática educativa (PIPE) nas licenciaturas em ciências biológicas, física e química : desafios e possibilidades para a formação docente - Silva, Andreia Pires da (2008)
The National Curriculum Guidelines for the training of teachers of the Basic Education Curriculum Reform established a for Undergraduate, in response to numerous problems presented in the field of teacher training. As part of this proposal, the introduction of 400 h / a Research and Practice for the Pedagogical since the start of the course, with the goal of working interdisciplinary, articulate theory and practice, articulate and educational expertise, caused some resistance on teachers As far as the specific contents of teaching. The Federal University of Uberlandia under the coordination of the Pro-Rector of Graduate / Board of Education, after numerous discussions, involving all Undergraduate, interpreted the law and produced its Institutional Project, which entered the Integrated Project Educational Practice (PIPE) , Which is now in our object of study. We focus in the courses of Bachelor of Biological Sciences, Physics and Chemistry, with the purpose of investigating how these courses organized their curricula to meet the existing legislation and how is the implementation of PIPEs. The approach used in the research was qualitative and collection of data made through the literature search, documentary and field. The data showed that the PIPE is a challenge for Undergraduate, and several strategies are being used in courses analyzed, to meet the specified working hours, without prejudice to the specific contents. Thus, under a variety of obstacles - epistemological, institutional, methodological and academic culture itself, the PIPE needs further clarification. Facing the difficulties encountered in its implementation, initiatives of the courses investigated are laudable, most are still far from answering the purpose intended for PIPEs.